Female directors and corporate reputation - Juan Carlos Navarro García; M. Camino Ramón-Llorens; Emma García-Meca (BRQ Business Research Quarterly, 2022)
This article analyzes the relationship between female directors and corporate reputation with a Spanish sample for the period 2008-2017. We also examine two background characteristics of women directors: their busyness and their educational background, suggesting that differences can exist among women according to their level of success (measured by the number of directorships) and their education. Our analyses show that female directors improve corporate reputation, but that neither women with multiple directorships nor the educational background of female directors increases corporate reputation, perhaps because stakeholders appreciate general attributes associated with women rather than the cognitive attributes of females on boards.
Keywords: M14; 650; busyness; Corporate governance; corporate reputation; educational background; female directors; M14